The Relationship of Parenting Styles of Parents and Exploration and Commitment in the Identity Formation of Occupations for Late Adolescents: A Study on the Identity Formation of Late Adolescents in the City and the Village - Ami Maryami (Asian Social Work Journal, 2018)
Ami Maryami, The Relationship of Parenting Styles of Parents and Exploration and Commitment on the Identity Formation of Occupations for Late Adolescents (A Study on the Identity Formation of Late Adolescents in the City and the Village). The research aims to find out 1) the relation of parenting styles of parents to exploration and commitment to the identity formation of occupations of late adolescents, 2) the different styles of parenting by parents, and 3) exploration and commitment differences on the identity formation of occupations of late adolescents, among those who live in the village and the city. The object of research is high school students who were in the third year (late adolescents) who live in Bandung Regency and the City of Bandung. The sampling technique used was two-cluster sampling, and n = 116 was obtained for late adolescents in the village and 116 for the late adolescents in the city. To examine the hypothesis in order to see whether it has a correlation or not, Pearson Correlation was used, while the t-test was used to see whether there were any differences. The research result revealed that there is a correlation between parenting styles of parents and exploration and commitment on identity formation of occupations of late adolescents who live in the village and the city. There is no difference in parenting styles of parents who live in the village and the city, and there is no difference in identity formation of occupations of late adolescents in the village and the city, but there is a difference in commitment in identity formation of occupations of late adolescents among those in the village and the city.